Linear widths of the classes B^Ω_p, θ of periodic functions of many variables in the space L_q - Fedunyk, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We obtain exact order estimates for the linear widths of the classes B^Ω_p, θ of periodic functions of many variables in the space L_q for certain values of the parameters p and q.